Ellipsometric investigation of β-Si₃N₄ ceramics with Mo and Al additives - Prokopets', V.M.; Shaykevich, I.A.; Robur, L.Y. (Functional Materials, 2005)
Ceramic Si₃N₄ samples with Мо and AI admixtures have been investigated by spectroellipsometry. The influence of admixtures on the ceramics optical properties have been studied. The local defects of Si₃N₄ crystal structure are responsible for the band gap reduction. The silicone oxynitride amount in the studied samples has been estimated numerically by Bruggeman effective medium approximation. Методом спектроэллипсометрии исследованы керамические образцы Si₃N₄ с добавками Мо и AI. Изучено влияние добавок на оптические свойства керамики. 3а сужение запрещенной зоны ответственны локальные дефекты кристаллической структуры Si₃N₄. Количество оксинитрида кремния в исследованных образцах численно оценено с применением приближения эффективной среды по Брюггеману. Методом спектроелiпсометрiї дослiджено керамiчнi зразки Si₃N₄ з домiшками Мо i AI. Вивчено вплив домiшок на оптичнi властивостi керамiки. 3а звуження забороненої зони вiдповiдають локальнi дефекти кристалiчної структури Si₃N₄. Кiлькiсть оксинiтриду кремнiю у дослiджених зразках оцiнено з застосуванням наближення ефективного середовища за Брюггеманом.